Pengaruh Pemberian Ekstrak Kulit Buah Cempedak ( Artocarpus Integer ) terhadap Pencegahan Penurunan Kadar Hemoglobin Pada Tikus Putih Jantan yang Dipapar Asap Rokok - Indah Ayudia, Esa; Tri Hardiningsih, Denok; Iksan, Pahrul; Harahap, Huntari; Putra Agung, Rhonaz (Jurnal Kesehatan Qamarul Huda, 2025)
The negative influence of the environment caused by smoking is free radicals. Cempedak plants contain active substances flavonoids, phenols, and tannins which are active substances that can function as antioxidants that can prevent free radicals. The purpose of the research was to find out the effect of cempedak fruit peel extract (Artocarpus integer) on the prevention of the decrease in hemoglobin levels in male white rats exposed to cigarette smoke. This type of research is quantitative analysistrue experimental using a completely randomized design withpretest and Posttest Control Group Design. The groups were divided into 6, namely the treatment group of 50 mg/kg, 100 mg/kg, 200/kg, the positive control of Vitamin E, the negative control, and the normal group. In several treatment groups there was no significant reduction in hemoglobin levels (p<0.05). The most significant increase in blood hemoglobin levels occurred in the treatment group with a dose of 200 mg/kgBW. The results of the study concluded that the giving of cempedak fruit peel extract (Artocarpus integer) is effective in preventing the decrease in hemoglobin levels in male white rats exposed to cigarette smoke.